Partisipasi Masyarakat dalam Upaya Pengembangan Objek Wisata Bukit Cinta Kawasan Rawa Pening Kecamatan Banyubiru Kabupaten Semarang - Pangaribuan, Larosa; Arifien, Moch. (Edu Geography, 2019)
The purpose of this research was to knowing how the stages of community participation, know what forms of community participation and how the tourism development approach is manifested in